2005
DOI: 10.1177/1471301205049192
|View full text |Cite
|
Sign up to set email alerts
|

Processes and experiences of mutual support in professionally-led support groups for people with early-stage dementia

Abstract: Participation in a support group is increasingly offered to those diagnosed with early-stage dementia; however, empirical data about such groups for this population remain scarce. This study aimed to investigate the mutual support processes that occur in dementia support groups and how members perceive the groups. Eleven individuals from two support groups participated; three sessions of each group were videotaped and semi-structured interviews were conducted with individual members. Quantitative analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 29 publications
1
58
1
1
Order By: Relevance
“…There is, however, little or no evidence on how to reflect optimally on the views and experiences of people with dementia when planning or evaluating services (Biernacki, 2000;Karel et al, 2007). In recent years, clinical and research interest in dementia has increased, including attempts to understand how a person with dementia experiences and perceives the onset of the illness and how they evaluate their quality of life (Mason, Clare, & Pistrang, 2005; see for example Clare, 2002aClare, , 2002bClare, , 2003Ettema, Dro¨es, de Lange, Mellenbergh, & Ribbe, 2005;Frank et al, 2006;Keady et al, 1995;Pearce, Clare, & Pistrang, 2002). The assessment of experience with care is regarded as a highly complex procedure of introspection and evaluation, involving several components of cognition including implicit and explicit memory (Thorgrimsen et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…There is, however, little or no evidence on how to reflect optimally on the views and experiences of people with dementia when planning or evaluating services (Biernacki, 2000;Karel et al, 2007). In recent years, clinical and research interest in dementia has increased, including attempts to understand how a person with dementia experiences and perceives the onset of the illness and how they evaluate their quality of life (Mason, Clare, & Pistrang, 2005; see for example Clare, 2002aClare, , 2002bClare, , 2003Ettema, Dro¨es, de Lange, Mellenbergh, & Ribbe, 2005;Frank et al, 2006;Keady et al, 1995;Pearce, Clare, & Pistrang, 2002). The assessment of experience with care is regarded as a highly complex procedure of introspection and evaluation, involving several components of cognition including implicit and explicit memory (Thorgrimsen et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This approach is being further developed with user-led groups for people with dementia (Pratt, Clare, & Aggarwal, 2005). Mason, Clare and Pistrang (2005) in their evaluation of mutual support processes that occur in support groups for people with dementia concluded that a support group for people soon after a diagnosis of dementia can be important for establishing social contacts and building an identity based on social ties with others in the group rather than on the difficulties encountered as a result of the dementia. One way of achieving this, they suggest, would be the opportunity to talk about everyday things and events that are unrelated to the experiences of living with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that meeting people in a similar situation and engaging in activities where people with dementia are accepted and not required to explain their disabilities improves their mood and morale (Mason, Clare, & Pistrang, 2005).…”
Section: Um Obviously Being Overwatched But I Think It Just Shows Tmentioning
confidence: 99%